A policy response to COVID-19: An Australian perspective. Issue 3 (3rd July 2021) - Stylianou, Vicki
ABSTRACT: The speed and scale of the public policy responses to the COVID-19 crisis in Australia have been breathtaking, in terms of health, social, and economic dimensions. Like many countries, initial policies were aimed at avoiding a "worst case" scenario and introduced social distancing restrictions, the closing of national and state borders, and the closing of "nonessential" businesses. These policies temporarily restricted the personal freedoms of Australians to reduce the potential for community spreading of the virus and, with it, the infection rate. Overall, these measures were relatively effective in controlling the public health impacts of the pandemic, and avoided the worst case scenarios initially envisaged. Now two key questions are how effective will the economic response be, and what will the implications be for the Australian economy going forward?